Blockchain-enabled asset-backed securitization and digital transformation in E-commerce supply chains: a game-theoretic approach - Yang, Lei; Shao, Junbo; Ye, Kunxin (Frontiers in Blockchain, 2025)
IntroductionThe development and growth of Asset-Backed Securitization (ABS) finance in the e-commerce supply chain is of great value in alleviating the capital constraints of enterprises. However, asset-backed securitization finance faces problems such as low cooperation efficiency and lack of trust mechanism. The consensus mechanism, encryption algorithm, traceability and other characteristics of blockchain can help strengthen cooperation between enterprises, improve the level of information sharing, and promote trust transmission. In the finance process, most managers are risk-averse, and managers are prone to overconfidence, overestimating returns and underestimating risks.MethodsThis paper studies asset-backed securitization finance in the e-commerce supply chain. Four models are constructed using game analysis: a non-cooperative model without blockchain, a cooperative model without blockchain, a non-cooperative model with blockchain, and a cooperative model with blockchain. The asset backed securitization finance strategy considering manager overconfidence and risk aversion with blockchain is analyzed to explore the optimal finance decision.Results and DiscussionThrough numerical analysis, it is found that blockchain helps to enhance the transparency and authenticity of financing information and increase the financing returns of e-commerce platforms. To a certain extent, the cooperation model can mitigate the negative impact of managers’ overconfidence on the financing returns of suppliers, e-commerce platforms and SPV. However, risk avoidance under the cooperative model is not conducive to the improvement of suppliers’ financing returns. The higher asset pool yield has significantly increased the financing returns of the SPV. The financing returns of suppliers and SPV will decline with the increase of the price sensitivity coefficient in the cooperative model, but it will be different in the non-cooperative model. This study strives to provide decision-making references for finance entities.